lncRNA UCA1 Predicts a Poor Prognosis and Regulates Cell Proliferation and Migration by Repressing p21 and SPRY1 Expression in GC - Xuezhi He; Jing Wang; Jin Chen; Liang Han; Xiyi Lu; Dengshun Miao; Dandan Yin; Qinghe Geng; Erbao Zhang (Elsevier, 2019)
Dysregulated expression of long non-coding RNAs (lncRNAs) has been reported in many types of cancers, indicating that it has important regulatory roles in human cancer biology. Recently, lncRNA urothelial cancer-associated 1 (UCA1) was shown to be dysregulated in many cancer types, but the detailed mechanisms remain largely unknown. In our study, we found that upregulated UCA1 is associated with poor prognosis in gastric cancer patients. Further experiments revealed that UCA1 knockdown significantly repressed the proliferation and migration both in vitro and in vivo. Moreover, RNA sequencing (RNA-seq) analysis revealed that UCA1 knockdown preferentially affected genes that are linked to cell proliferation, cell cycle, and cell migration. Mechanistically, UCA1 promotes cell proliferation progression through repressing p21 and Sprouty RTK signaling antagonist 1 (SPRY1) expression by binding to EZH2. We found that UCA1 could mediate the trimethylation of H3K27 in promoters of p21 and SPRY1. To our knowledge, this is the first report showing the global gene profile of downstream targets of UCA1 in the progression of gastric cancer. Collectively, our data reveal the important roles of UCA1 in gastric cancer (GC) oncogenesis. Keywords: UCA1, cell proliferation, cell migration, p21, SPRY1